Nimotuzumab combined with concurrent chemoradiotherapy in Japanese patients with esophageal cancer: A phase I study. Issue 3 (15th February 2018) - Kato, Ken; Ura, Takashi; Koizumi, Wasaburo; Iwasa, Satoru; Katada, Chikatoshi; Azuma, Mizutomo; Ishikura, Satoshi; Nakao, Yoshinori; Onuma, Hiroshi; Muro, Kei
Abstract : Nimotuzumab is a humanized anti‐epidermal growth factor receptor IgG1 monoclonal antibody. This phase I study assessed the tolerability, safety, efficacy, and pharmacokinetics of nimotuzumab in combination with chemoradiotherapy in Japanese patients with esophageal cancer. Patients with stage II, III, and IV esophageal cancer were enrolled. Patients were planned to receive nimotuzumab (level 1: 200 mg/wk for 25 weeks; or level 2: 400 mg/wk in the chemoradiation period, 400 mg biweekly in an additional chemotherapy period [8 weeks after the chemoradiation period] and a maintenance therapy period [after chemotherapy to 25 weeks]) combined with cisplatin (75 mg/m 2 on day 1) and fluorouracil (1000 mg/m 2 on days 1‐4) in the chemoradiation and additional chemotherapy periods. Radiotherapy was given concurrently at 50.4 Gy. A total of 10 patients were enrolled in level 1. Dose‐limiting toxicities were observed in 2 patients (grade 3 infection and renal disorder). Maximum‐tolerated dose was estimated to be at least 200 mg/wk and the dose was not escalated to level 2. The most common grade ≥3 toxicities were lymphopenia (90%), leukopenia (60%), neutropenia (50%), and febrile neutropenia, decreased appetite, hyponatremia, and radiation esophagitis (30% each). Neither treatment‐related death nor grade ≥3 skin toxicity was observed in any patient. Complete response rate was 50%. Progression‐free survival was 13.9 months. One‐ and 3‐year survival rates were 75% and 37.5%, respectively. Immunogenicity was not reported in any patient. Nimotuzumab in combination with concurrent chemoradiotherapy was tolerable and effective for Japanese patients with esophageal cancer. Abstract : In this phase I study, we assessed the tolerability, safety, efficacy, and PK of nimotuzumab (200 mg/wk; determined to be the maximum‐tolerated dose) in combination with chemoradiotherapy in Japanese patients with esophageal cancer. The most common grade ≥3 toxicities were lymphopenia (90%), leukopenia (60%), and neutropenia (50%). Nimotuzumab in combination with concurrent chemoradiotherapy was tolerable and effective for Japanese patients with esophageal cancer.